If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-3) + 3y = 27 Multiply 4 * -3 -12 + 3y = 27 Solving -12 + 3y = 27 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3y = 27 + 12 Combine like terms: -12 + 12 = 0 0 + 3y = 27 + 12 3y = 27 + 12 Combine like terms: 27 + 12 = 39 3y = 39 Divide each side by '3'. y = 13 Simplifying y = 13
| 2(.9x-1.5)=18.6 | | X+(7-x)=7 | | 2(x+6)-2=16-5x-6+7x | | 2(0.9x-1.5)=18.6 | | -5+7(x-4)=15x+2-8x | | (4x-1)2=1499 | | 7(a-7)+13=5(a-6) | | 8x-9=6x+13 | | 28x-7=49 | | 12x^2-176x+480=0 | | 1=1/3a-5 | | 4=2.6x | | 3(17)-(9n)=24 | | 2ln(x-2)-ln(x^2-4)+ln(3)=0 | | -2(y-3)+y=12 | | 5f+2=-4+2f-8 | | 2.75+.003+.158=2.938 | | 9m-2m=77 | | 4g+g=12 | | 3a-2a=12 | | 4xz=2104 | | 700/15 | | 3x+x=1 | | 1/cotu | | 5f+2=-42f-8 | | 2sectheta-2/1-costheta=2sectheta | | n+72=180 | | 6a+9=8 | | 55b^2-155b-30= | | 50/y=y/2 | | Mx=8 | | -31-3p=7+4(8+8p) |